Urinary Stents 2022
DOI: 10.1007/978-3-031-04484-7_18
|View full text |Cite
|
Sign up to set email alerts
|

Coatings for Urinary Stents: Current State and Future Directions

Abstract: Urinary stent coatings are a strategy to tackle certain complications associated with the use of biomaterials. The latest innovations in surface coatings focused on the prevention of those problems, thus reducing further costs with treatments. Urinary stents associated symptoms, infections and encrustation are considered the major challenges, and, in an attempt to prevent such morbidity, several strategies were developed. Hence, coatings have been designed to improve quality of life for patients, reducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…Surface modification Cellobiose deshydrogenase (CDH) CDH was covalently grafted onto plasma-activated urinary polydimethylsiloxane (PDMS) catheter surfaces. S. aureus [433] Metals or composite nanoparticles represent suitable alternatives for CA-UTI prevention and biofilm-related infections [434]. Several studies [409,[435][436][437][438][439] have reported that UCs coated with thin-films of silver alloy could reduce bacterial adhesion but also the incidence of asymptomatic bacteriuria and CA-UTI.…”
Section: P Aeruginosa [432]mentioning
confidence: 99%
See 4 more Smart Citations
“…Surface modification Cellobiose deshydrogenase (CDH) CDH was covalently grafted onto plasma-activated urinary polydimethylsiloxane (PDMS) catheter surfaces. S. aureus [433] Metals or composite nanoparticles represent suitable alternatives for CA-UTI prevention and biofilm-related infections [434]. Several studies [409,[435][436][437][438][439] have reported that UCs coated with thin-films of silver alloy could reduce bacterial adhesion but also the incidence of asymptomatic bacteriuria and CA-UTI.…”
Section: P Aeruginosa [432]mentioning
confidence: 99%
“…Other antibiotics such as gentamicin [453], chlorhexidine [454], ciprofloxacin [455], norfloxacin [456], triclosan [457], and sparfloxacin [418] have been tested as a coating agent. Although giving promising results, the antibiotic-based approach favors the apparition of bacterial resistance for long-term catheters (e.g., triclosan), leading to more serious infections [434,458].…”
Section: P Aeruginosa [432]mentioning
confidence: 99%
See 3 more Smart Citations